Development of Chitosan/Poly(Vinyl Alcohol) Electrospun Nanofibers for Infection Related Wound Healing - Wang, Mian; Roy, Amit K.; Webster, Thomas J. (Frontiers in Physiology, 2017)
Chitosan is a cheap resource, which is widely used in biomedical applications due to its biocompatible and antibacterial properties. In this study, composite nanofibrous membranes of chitosan (CS) and poly(vinyl alcohol) (PVA) loaded with antibiotics at different ratios were successfully fabricated by electrospinning. The composite nanofibers were subjected to further analysis by scanning electron microscopy (SEM). SEM images revealed that the volumetric ratio of CS/PVA at 50/50 achieved an optimal nanofibrous structure (i.e., that most similar to natural tissues) compared with other volumetric ratios, which indicated that this CS/PVA electrospun scaffold has great potential to be used for infection related wound dressing for skin tissue regeneration.